I am Slappy's evil twin - Stine, R. L. (New York, NY : Scholastic Inc., 2017)
Luke Harrison's dad makes horror movies. It's very fun to be around such scary stuff-especially when you have your own monster museum at home. But when two ventriloquist dummies join the collection, things get real creepy. Real-life creepy! Slappy and Snappy can walk and talk on their own.
Contains excerpt of the next Goosebumps Slappyworld series.
Appeals to 4th-6th graders.
Reading level grade 4.
Accelerated Reader AR
Keywords: Ventriloquists' dummies -- Juvenile fiction; Horror tales -- Juvenile fiction; Ventriloquists' dummies -- Fiction; Horror stories; Juvenile Fiction -- Horror; Juvenile Nonfiction -- Humor; Ventriloquists' dummies -- Juvenile fiction; Ventriloquists' dummies -- Fiction; Ventriloquists' dummies; Fiction; JUVENILE FICTION -- Horror; JUVENILE NONFICTION -- Humor; Horror tales; Ventriloquists' dummies; Horror stories; Ventriloquists' dummies -- Fiction; Horror stories; Juvenile works; Horror tales -- Juvenile fiction; Horror fiction; Horror tales; Fiction; Horror fiction; Juvenile works; Horror fiction; Horror fiction